PENINGKATAN MUTU DAN RELEVANSI PENDIDIKAN - Waruwu, Henoki (DIDAKTIK, 2008)
Abstract: The quality of education is a must, however, in Indonesia it is only a imagination. Therefore, the government strives to develop the quality of education in various policies. Besides the effort, the quality of education can not be also separated from the link and match of business. In this case, the effort of developing of the quality of education must be oriented on the link and match of business.Â Key words: Education, Quality, Relevance.